2013
DOI: 10.1002/pi.4639
|View full text |Cite
|
Sign up to set email alerts
|

Macromolecular and supramolecular chirality: a twist in the polymer tales

Abstract: Introducing chiral hierarchical structures in polymer materials and polymer surfaces unlocks additional properties and functionalities in a range of applications in nanoscience, biomedicine and biomaterials. (All M.C. Escher works © 2013 The M.C. Escher Company ‐ the Netherlands. All rights reserved. Used by permission. http://www.mcescher.com.)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…It is well known that twist is a chiral property and arises from chirality at some level of organization of substances, usually arising from molecular chirality. Many studies of twist and its chiral roots have been published and some studies of biological polymers have pointed back to the chiral centers in the polymers as the source of twist(de Bruin, Barbour & Briscoe, 2014;Fujiki, Koe, Terao, Sato, Teramoto & Watanabe, 2003;Khandelwal & Windle, 2014a;Lotz & Cheng, 2005). The chiral centers, however, and their specific chirality cannot determine the direction of twist or degree of twist in a polymer since there are other contributing factors, such as orientation of molecular associations.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that twist is a chiral property and arises from chirality at some level of organization of substances, usually arising from molecular chirality. Many studies of twist and its chiral roots have been published and some studies of biological polymers have pointed back to the chiral centers in the polymers as the source of twist(de Bruin, Barbour & Briscoe, 2014;Fujiki, Koe, Terao, Sato, Teramoto & Watanabe, 2003;Khandelwal & Windle, 2014a;Lotz & Cheng, 2005). The chiral centers, however, and their specific chirality cannot determine the direction of twist or degree of twist in a polymer since there are other contributing factors, such as orientation of molecular associations.…”
Section: Introductionmentioning
confidence: 99%
“…Twisted architecture widely arises in nature from molecules to nano- and microscale materials to macroscopic objects such as DNA, RNA, peptide, and chromosome. , Such twisted architectures play an important role in improving mechanical properties as well as enabling biological functions. Inspired by the beauty and interesting properties of twisted structures, a wide range of artificial chiral materials with twisted or coiled structures have been prepared, from organic and inorganic nanorods, nanotubes, and nanobelts to macroscopic architectures and buildings. , …”
Section: Introductionmentioning
confidence: 99%
“…Delivery systems of controllable size and definable molecular response to stimuli are of great importance in the field of polymeric biomaterials where they are expected to induce specific biological responses. Block copolymers can be built from a plethora of polymeric building blocks linked by a variety of chemical connections …”
Section: Introductionmentioning
confidence: 99%
“…Block copolymers can be built from a plethora of polymeric building blocks linked by a variety of chemical connections. 6 One of the very first reports on the self-assembly of pentablock copolymers was published by Jones and colleagues 7 and indicates the ability of the poly(ethylene oxide)-poly(methylphenylsilane) amphiphilic multiblock copolymer to self-assemble into vesicles. Mallapragada and colleagues have utilized the self-assembly capabilities of pentablock copolymers in biomedical applications and have shown that their poly(amino methacrylate) terminated Pluronics form micelles and gels that lend themselves as non-viral vectors for gene delivery 8 and as polymer adjuvants for the controlled and sustained delivery of protein vaccines 9 using the block copolymers' pH and temperature dependent phase behavior.…”
Section: Introductionmentioning
confidence: 99%